Optimization the production and processing of agricultural production in horizontal-integrated system - Kabdulsharipova, А.М.; Suieubayeva, S.N.; Dzhempeisova, G.I. (KSU Publ., 2016)
Effective development of agro-industrial complex of Kazakhstan in the conditions of the competitive pressure and external social and economic threats isn't possible without implementation of new system forms of the organizational decisions which are based on the principles of integration and cooperation. The article substantiates the need for horizontal integration of agricultural production. Optimization of process of a feed production as main technological process in livestock production is offered. Calculations for optimization of the main technological process, namely, a forage production which purpose is security of livestock production with various sterns are carried out: mineral, vegetable and animal origin. The model of the horizontally integrated business process of production of grain was calculated on the basis of imitating modeling. The optimum plan is received as a result of optimizing calculations with application of a simplex method of linear programming. The integrated production of agricultural production is the effective solution of recovery from the crisis of agrarian sector of economy.
Деңгейлес-біріктірілген жүйеде ауылшаруашылық өнімді өндіру жəне өңдеуді оңтайландыру
Оптимизация производства и переработки сельхозпродукции в горизонтально-интегрированной системе
Keywords: horizontal integration; agricultural production; optimization the production; a simplex method of linear programming